2017
DOI: 10.22219/jp2sd.v5i2.4820
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomathematica Dalam Pembelajaran Matematika (Pembelajaran Bilangan Dengan Media Batik Madura, Tari Khas Trenggal Dan Tari Khas Madura)

Abstract: Cultural-based mathematics learning is a model of learning approach that prioritizes students' activities with a variety of cultural backgrounds, which are known as ethnomathematica. In this article will be elaborated mathematical activities that use cultural background. Therefore, this paper will describe a) how the application of ethnomathematica in mathematics learning, b) how the number of learning with batik madura, typical trenggal dance and typical madura dance.Keyword: learning mathematics, batik madur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
7
0
7
Order By: Relevance
“…while the back side was a picture of the number of dancers or motifs of Batik Madura (Madurese batik motifs). In Ekowati et al research, they revealed that there were advantages in the application of ethnomatematics with the Madura batik media, traditional trenggal dances and Madurese special dances in learning, because they could deepen students' understanding of the topic of numbers [27]. This research also showed that mathematical activities that were usually considered abstract by students became more concrete by being associated with elements of local culture.…”
Section: Angkatahun Templementioning
confidence: 88%
See 1 more Smart Citation
“…while the back side was a picture of the number of dancers or motifs of Batik Madura (Madurese batik motifs). In Ekowati et al research, they revealed that there were advantages in the application of ethnomatematics with the Madura batik media, traditional trenggal dances and Madurese special dances in learning, because they could deepen students' understanding of the topic of numbers [27]. This research also showed that mathematical activities that were usually considered abstract by students became more concrete by being associated with elements of local culture.…”
Section: Angkatahun Templementioning
confidence: 88%
“…For grade I students, the head of the kala is suitable as a learning object for counting because the fingers formed on the relief of Kepala Kala are the symbol of number 2. Angkatahun relief is a Javanese number, in learning in school teachers can introduce Javanese numbers through learning media in the form of cards as has been done by Ekowati et al [27]. The card was made with two sides, the front side is a symbol of mathematical numbers in general (1,2,3,4, etc.)…”
Section: Angkatahun Templementioning
confidence: 99%
“…Kesadaran nilai pendidikan memaknai bahwa nilai tidak diajarkan, melainkan ditangkap atau dirasakan (Soemantri, 2019). Siswa belajar dari contoh yang diberikan pendidiknya (Ekowati et al, 2017). Menjadi sangat penting bagi tiap pendidik agar mampu menjadi teladan dengan menyadari dan terus menghidupkan nilai pribadi siswa (Lewis, 2002).…”
Section: Pendahuluanunclassified
“…Indicators of understanding accurate mathematical concepts must also be mastered by elementary school pre-service teachers at the University of Muhammadiyah Malang. This is due to the teacher candidates who will later give the accurate concept to the next generation (Ekowati et al, 2017) (Mizan, 2019). In order to meet these expectations, one of the mathematics learning achievements shows that students must be able to apply elementary mathematics learning theories and conceptual knowledge of mathematics in the form of making elementary mathematics learning plans with full responsibility.…”
Section: Introductionmentioning
confidence: 99%